Which venture capital backed entrepreneurs have the best chances of succeeding? - Dubini, Paola (Journal of Business Venturing, 1989)
This paper examines the common behavioral characteristics of entrepreneurs backed by venture capital companies; the results will hopefully prove helpful to venture capitalists in their screening process. Some authors (Timmons, Swollen and Dingee 1977) assume that the success of a new venture is influenced by the fit between entrepreneurial team characteristics and product and market characteristics. If this is the case, it is crucial for venture capitalists to evaluate not only team characteristics and product/market characteristics separately, but also such fit before deciding to invest in a project. Venture capitalists have excellent capabilities for assessing product and market assumptions, which are easier to measure than behavioral characteristics. The evaluation of the management team is therefore their most challenging task in the venture selection process. Goslin and Barge (1986) reported that management team and entrepreneurial qualities have a greater impact than any product and market considerations on the venture capitalist's selection process. The purpose of this study is to determine which entrepreneurial team characteristics are useful predictors of performances, given product and market characteristics of the new venture. The research was conducted using the data base of MacMillan, Zemann and SubbaNarasimha (1987), who collected data for successful and unsuccessful ventures relating to the entrepreneurial team, product/service characteristics, market characteristics, and venture performance characteristics. A sample of 151 ventures rated by venture capitalists was cluster analyzed on the basis of product/service and market characteristics, in the expectation that different types of ventures in different contexts would call for different venture team or entrepreneurial characteristics. Four very different clusters were identified. Once cluster analysis was completed, regression analysis was run for each cluster to determine the entrepreneurial team characteristics most significant in predicting different performance variables. It was expected that different entrepreneurial team characteristics would be significant for each cluster. The results show that this is generally the case. On the whole, adjusted R-square values were encouragingly high and highly significant, indicating that different entrepreneurial characteristics were good predictors of performance for given product and market combinations. Moreover, there was an equally encouraging consistency of significant predictors across all the performance variables tested.